Answer:
4n^3 +n +7
Step-by-step explanation:
(5n^3+7n+2)+(-n^3-6n+5)
I like to line them up vertically
5n^3+7n+2
-n^3 -6n+5
-----------------------
4n^3 +n +7
Answer:
Step By Step Explanation:
Remove Parenthesis: (a) = a
Group Like Terms
Combine Similar Elements:
Combine Similar Elements:
Add:
➤
Y=3x-13
3x+2y=19
The solution to the system of equations is x = 5 and y = 2.
Given that:
The system of equations:
y = 3x - 13 (1)
3x + 2y = 19 (2)
Step 1: Solve equation (1) for Y:
y = 3x - 13
Step 2: Substitute y from equation (1) into equation (2):
3x + 2(3x - 13) = 19
Step 3: Simplify the equation and solve for x:
3x + 6x - 26 = 19
9x - 26 = 19
9x = 19 + 26
9x = 45
x = 45/9
x = 5
Step 4: Substitute x = 5 into equation (1) to find Y:
y = 3(5) - 13
y = 15 - 13
y = 2
So, the values of x and y are 5 and 2, respectively.
Learn more about Equation here:
#SPJ6
b) 1:4
c) 20:3
d) 4:1